Visão de maloqueiro: uma carta sobre as juventudes pretas faveladas, o funk e a saúde mental - Andrade, Paula Fernanda de (Universidade Federal de São Carlos, 2023)
In Brazil, one of the biggest cultural movements of peripheral youth in the 20th and 21st centuries is Funk, which emerged from urban popular culture, mainly in the states of Rio de Janeiro and São Paulo. The funk movement aims to contest and challenge the hegemonic system, through music, dance, “dances” and its own aesthetics, evidenced by clothes, haircuts and accessories, popularly called “kit”. The central figure of funk culture is the boy, black, poor and from the favelas, who, contrary to the silencing structure in which he is daily inferiorized and segregated, through funk performance in search of protagonism. This protagonism can be read concretely in most funk lyrics. We could affirm that through funk, these young people exercise their cultural citizenship rights on a daily basis, as Chauí (2008) has proposed, as they actively insert themselves in their territories, produce themselves as subjects and invent forms of social participation in cultural circuits and politicians.This research aims to understand how black, peripheral and funk culture has produced the possibility of existence, creation and transformation of realities. As well as highlighting how the production of mental health occurs in this context, understanding here, mental health not as the absence of a disorder or illness, but as the experience of citizenship itself, subjectivation and the possibility of existing and creating new experiences and spaces of belonging in the world, that is, in the sense of the collective production of subjectivity. For this, methodologically, intervention research was used, with cartographic reference based on the interview technique to produce data in dialogue with the concept of Writing by the author Conceição Evaristo. Six self-declared young participants, black, peripheral and funk fans, were interviewed. The results were presented based on eight dimensions: (1) characterization of participants, (2) Conceptions of mental health, (3) Black emotionality, (4) Memories, belongings and records, (5) Collective and political action, ( 6) the body, corporeality and the aesthetic dimension, (7) Racism and everyday life and (8) Negritude, funk and the field of mental health. It concludes that the field of mental health is urgently positioned to contribute to the promotion of racial equity and the deinstitutionalization of racism, which David and Vicentin (2020) called the Aquilombamento process. In this sense, funk cultural production needs to be highlighted in this field, since it presents itself as a powerful expression of the ethical, aesthetic and political dimensions of the mental health of the young black Brazilian population, and points us to clues for the production of care practices and of social transformation.
Visão de maloqueiro: a letter about black youth in the favelas, funk, and mental health
Visão de Maloqueiro: Una carta sobre las juventudes negras en las favelas, el funk y la salud mental
Keywords: Saúde mental; Racismo; Cultura; Reforma psiquiátrica; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL